Protective efficacy of a novel simian adenovirus vaccine against lethal MERS-CoV challenge in a transgenic human DPP4 mouse model. (December 2017) - Munster, Vincent; Wells, Daniel; Lambe, Teresa; Wright, Daniel; Fischer, Robert; Bushmaker, Trenton; Saturday, Greg; Doremalen, Neeltje; Gilbert, Sarah; Wit, Emmie; Warimwe, George
Abstract Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel zoonotic virus that causes severe respiratory disease in humans with a case fatality rate close to 40%, but for which no vaccines are available. Here, we evaluated the utility of ChAdOx1, a promising replication-deficient simian adenovirus vaccine vector platform with an established safety profile in humans and dromedary camels, for MERS-CoV vaccine development. Using a transgenic lethal BALB/c MERS-CoV mouse model we showed that single dose intranasal or intramuscular immunisation with ChAdOx1 MERS, encoding full-length MERS-CoV Spike glycoprotein, is highly immunogenic and confers protection against lethal viral challenge. Immunogenicity and efficacy were comparable between immunisation routes. Together these data provide support for further evaluation of ChAdOx1 MERS vaccine in humans and dromedary camels, the animal reservoir of infection.